A model for partner selection criteria in energy from waste projects. (10th January 2021) - Uren, Victoria; Miller, Tim; Da Campo, Raffaello; Dadzie, Aba-Sah
Abstract: Energy from Waste is being deployed in both developed and developing economies as a route to reduce dependency on fossil fuels whilst making positive use of resources which might otherwise be landfilled. Energy from Waste supply chains are complex, with a rich diversity of partners and stakeholders involved. For this purpose, the selection of appropriate criteria to guide supply chain design, and in particular the selection of suppliers, is critical for success. In this study, a three-stage process was conducted to identify, refine and validate an evidence-based model. The evidence based model proposed comprises seven categories of criteria used in the design of these supply chains, namely Economic, Environmental, Location, Operations management, which has a sub-category of Plant operation, Political/Legal and Social. The work reported here supports practitioners and researchers involved in supply chain partner selection to systematise their thinking in relation to the criteria that may impact their study or project.